Pengaruh Kombinasi Media Tanah dan Pasir Terhadap Penurunan Kadar BOD dan COD pada Limbah Domestik Rumah Makan dengan Sistem Wetland Menggunakan Tumbuhan Cyprus - Lily Oktavia; Catur Lega Wibisono; Muchammad Tamyiz (University of Halu Oleo, 2021)
The development of restaurant businesses in Sidoarjo City is quite rapid, and this will of course be accompanied by an increase in domestic waste originating from a restaurant called greywater. Restaurant wastewater contains a lot of organic content and often without prior treatment is discharged directly into receiving water bodies. The purpose of this study was to determine the reduction in BOD and COD levels for the processing of restaurant wastewater using a contructed wetland with Cyperus Rotundus as the remediator. The research stage will be carried out using a laboratory scale using acclimatization as the adaptation stage of the Cyperus Rotundus plant and the crontructed wetland reactor as phytoremediation processing. Based on the results and discussion, it can be concluded that there was a decrease in BOD and COD levels in restaurant liquid waste using the Constructed Wetland System and Cyperus Rotundus plants. The percentage reduction in the largest BOD content in clay media with the number of Cyperus Rotundus plants of 3 stems gave the highest BOD removal efficiency, namely 70% at 4 days of detention time. While the largest percentage reduction in COD levels in clay media with the number of Cyperus Rotundus plants as many as 3 stems gave the highest COD removal efficiency, namely 67% at 4 days detention time.